Perlindungan Konsumen Terhadap Informasi Menyesatkan Mengenai Suatu Barang Pada Kegiatan Perdagangan Elektronik - Finna Nazran (Universitas Medan Area, 2020)
Transactions in e-commerce are very risky, especially because consumers have an obligation to make payments in advance, while consumers themselves cannot see the truth of the goods ordered or the quality of the ordered goods. The aspects of actions that are prohibited for business actors in the UUPK are regulated in Article 8 to Article 17. In an e-commerce sale and purchase agreement, business actors are obliged to provide true and clear information about the condition of the goods being offered and provide detailed information about the condition of the goods. how to use it or use it. The research method used is prescriptive normative juridical research where this research seeks to provide an overview or formulate a problem in accordance with circumstances or facts related to existing benchmarks / norms. As for the form of responsibility, if it is related to responsibility in Article 19 of the UUPK, the implementation of compensation in the UUPK is 7 days after the agreement. Providing compensation in e-commerce provides a period of giving compensation for 7 days after the goods are received by consumers